THE LIVING TRADITION OF “BAY’AH LIMA”: Sustaining Sheikh Musthafa Husein al Mandily’s Teachings in Shaping Santri Nationalism - Musa, Faisal; Asari, Hasan; Abdul Hamid, Ahmad Fauzi; Rosyadi, Budiman (State Islamic University North Sumatra, 2025)
This paper examines the living tradition of Bay’ah Lima, rooted in the teachings of Sheikh Musthafa Husein al-Mandily, with particular attention to its historical development and transformation. Using a qualitative-historical approach and drawing on Eric Hobsbawm’s theory of Invented Tradition, the study highlights three key findings: first, Bay’ah Lima emphasizes loyalty to both religion and the nation; second, while the formal practice of oath-taking is no longer observed in Pesantren Musthafawiyah, it has evolved into forms more relevant to contemporary contexts; and third, its values remain embedded in classroom teaching, pesantren activities, and national commemorations. These findings illustrate that traditions may shift in form while retaining their essence. The study underscores the role of pesantren as a vital force in shaping Indonesian nationalism, countering assumptions that Islamic education fosters anti-nationalist sentiment, and recommends that pesantren continuously contextualize their practices to sustain both religious and national consciousness.